OPTIK GENDER DALAM PUTUSAN PERKARA KEKERASAN FISIK DALAM RUMAH TANGGA - Velliana Tanaya (Komisi Yudisial RI, 2011)
ABSTRACTDomestic violence is such a lot happened phenomenon that it has become quantitatively an object in a court case after the enactment of Act Number 23 year 2004. One important aspect associated with this criminal act is that the victims are almost entirely women, by and large in a position as a wife. Analysis of the decision of District Court of Tangerang does not only highlight on the provision of formal and material aspects of the criminal law, but also consider the perspective of gender equality, which should be put as an initial point for the legal reasoning of the panel of judges.Key words: domestic violence, gender equality, victim ABSTRAKLonjakan perkara Kekerasan rumah tangga di pengadilan meningkat tajam semenjak pengesahan Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. Salah satu aspek yang penting dalam terkait dengan tindak pidana adalah korban selalu di pihak perempuan, dan kebanyakan mereka sebagai isteri. Terkait hal itu, analisa dalam putusan dari Pengadilan Negeri Tangerang tidak hanya mengedepankan ketentuan formal dan materiil dalam hukum pidana sebagai permulaan alasan hukum oleh majelis hakim, namun juga mempertimbankan pandangan kesamaan gender. Kata kunci: kekerasan rumah tangga, persamaan gender, korban.